Sobre estruturas linguísticas e paradigmas: as releituras recentes de Carnap e Kuhn - Silva, Gilson Olegario da (2013)
e recent literature in philosophy of science has been reassessing the positivist legacy. One of the items on the agenda is the alleged opposition between the theses put forth by positivists such as Carnap and the so-called post-positivists , such as Kuhn. Although the laer came to be viewed as a critic of several important positivist theses, more recent authors such as Friedman, Reisch, Earman, Irzik and Grünberg, maintain that several of the most characteristic theses of the Kuhnian view of science were already present in Carnap s philosophy. Against this kind of reading, authors such as Oliveira and Psillos argue that within Carnap s philosophy there is no place for Kuhnian theses like incommensurability, holism or the theoryladenness of observations. e first article of this dissertation presents the reasons for each of those readings and assesses them having in view the perspectives from which they are offered. It argues that it is possible to show that some aspects of Kuhn s thesis have a counterpart in the works of Carnap, although those theses vary in importance for Carnap and Kuhn. e second article presents aspects that can be seen as antagonistic in the two views, namely, the conceptions that relate to that distinction made famous by Reichenbach between contexts of discovery and justification.